2005
DOI: 10.1212/01.wnl.0000160115.55756.de
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vascular dementia in the Cardiovascular Health Cognition Study

Abstract: Vascular disease in the brain is prevalent among incident dementia cases. There is a substantial overlap between cases classified as Alzheimer disease by Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association and vascular dementia (VaD) by modified State of California Alzheimer's Disease Diagnostic and Treatment Centers criteria. The substantial contribution of vascular disease would be missed without inclusion of MRI. Treatment of risk factors for VaD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
2
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 24 publications
6
101
2
6
Order By: Relevance
“…Other studies have confirmed the relationship between hypertension, heart disease, diabetes, stroke and AD [55][56][57][58][59][60][61][62]. Our study confirmed that hypertension is a risk factor for early onset AD [63].…”
Section: Comorbiditiessupporting
confidence: 88%
“…Other studies have confirmed the relationship between hypertension, heart disease, diabetes, stroke and AD [55][56][57][58][59][60][61][62]. Our study confirmed that hypertension is a risk factor for early onset AD [63].…”
Section: Comorbiditiessupporting
confidence: 88%
“…A number of factors are known to increase the risk of vascular dementia, including a history of hypertension, DM, hyperlipidemia, smoking and cardiac conditions [2][3][4]. Several studies have addressed the contribution of each risk factor to VaD and the question 1 These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Fish consumption is associated with decreased risk of dementia and cognitive decline, 5 for which major risk factors are subclinical brain abnormalities. 6 We hypothesized that, as with overt infarcts, 4 consumption of tuna/other fish would be associated with lower risk of subclinical infarcts among older adults, while fried fish consumption would be associated with higher risk. We also investigated associations of fish consumption with MRI-defined white matter abnormalities and ventricular and sulcal enlargement.…”
mentioning
confidence: 99%